A confirmatory factor analysis of the revised illness perception questionnaire (IPQ-R) in a cervical screening context. - Hagger MS; Orbell S (Psychology & Health, 2005)
The purpose of the present study was to test the factorial and discriminant validity of the Revised Illness Perception Questionnaire (IPQ-R), a measure of illness representations based on Leventhal, Meyer and Nerenz's Self-Regulation Theory, in a cervical screening context using confirmatory factor analysis. Six hundred and sixty women, who had attended a colposcopy clinic and were invited to re-attend, completed the IPQ-R. Data were analysed using covariance structure analysis. The adequacy of an a priori confirmatory factor analytic model that included seven dimensions of the cognitive illness representation: identity, timeline-acute/chronic, serious consequences, personal control, treatment control, illness coherence, and causal attributions, and one emotional representation factor was tested against the observed data. After the elimination of two items responsible for large standardised residuals and with low factor loadings, the model adequately accounted for covariances among the IPQ-R items according to multiple criteria for goodness-of-fit. Factor inter-correlations supported the discriminant validity of the constructs and the factors exhibited satisfactory composite reliability. A theoretically predictable pattern of relationships among the representation dimensions was evident. In particular, the control-related constructs and the illness coherence dimension were negatively related to other illness representation constructs. The present study provided confirmatory evidence using a robust hypothesis-testing framework to support the proposed structure of the illness representation dimensions in a cervical screening context.